Finnish matriculation examination’s exam in Social Studies – an appropriate gatekeeper and competence support? - Kupiainen, Sirkku; Ouakrim-Soivio, Najat; Hanska, Jussi (JSSE - Journal of Social Science Education, 2023)
The study set to investigate the Finnish matriculation examination with a focus on the social studies. The goal was to examine how well the subject-specific exams of the examination measure students’ attainment in the courses of the respective subject across upper secondary studies. The data was drawn form a longitudinal study of 6,172 Southern-Finland upper secondary students in 62 schools who passed their matriculation examination in spring 2017. Data on course choices and attainment was received from school and matriculation examination results from the Finnish Matriculation Examination Board. Key finding of the study is the unanimity between the two assessments: students’ grades in the subject-specific exams of the matriculation examination correlated strongly with their respective grades across the courses during their three years of upper secondary studies. The findings give strong support for the matriculation examination as an exit exam and for its use in student admission to higher education. Corresponding author: Najat Ouakrim-Soivio, Mannerheiminkatu 2, 06100 Porvoo, Finland. najat@arviointi.fi: https://orcid.org/0000-0001-9139-4145 Suggested citation: Kantasalmi, K., & Kupiainen, S. (2021). Classes with selective intake in Finnish Comprehensive School: A Problem of Societally Equal Opportunity for Schooling or a Boost for Learning and Equity in Pedagogical arrangements? International Journal of Educational Research, 109, 101857. Kupiainen, S. & Hotulainen, R. (2017). Metropolialueen nuoret toisen asteen opiskelijoina: osaamisen ja oppimisasenteiden kehitys yläkoulun alusta lukion ja ammatillisten opintojen toisen opiskeluvuoden kevääseen. [The metropolitan youth as upper secondary students: The development of learning and learning attitudes from the beginning of lower secondary studies to the second year of general or vocational upper secondary studies]. In A. Toom, M. Rautiainen & J. Tähtinen (Eds.) Toiveet ja todellisuus – Kasvatus osallisuutta ja oppimista rakentamassa. Kupiainen, S., Marjanen, J., & Hautamäki, J. (2016). The problem posed by exam choice on the comparability of results in the Finnish matriculation examination Journal for Educational Research Online, 8(2), 87. Retrived 15.10.2022 at https://www.waxmann.com/index.php?eID=download&id_artikel=ART102868&uid=frei Kupiainen, S., Marjanen, J. & Ouakrim-Soivio, N. (2018). Ylioppilas valintojen pyörteessä. [The matriculate in the whirlwind of choices]. Suomen ainedidaktisen tutkimusseuran julkaisuja. Ainedidaktisia tutkimuksia 14. Retrived 15.10.2022 at https://helda.helsinki.fi/handle/10138/231687 Ouakrim-Soivio, N., Kupiainen, S., & Marjanen, J. (2017). Toimivatko oppilas- ja opiskelija-arvioinnin kriteerit? Oppiaineiden välinen ja sukupuolen mukainen vaihtelu perusopetuksen ja lukion päättöarvosanoissa ja arvosanojen yhteys nuorten oppiainevalintoihin. [How do the criteria for student assessment work? Subject and gender-based variation in students’ final grades and their relation to students’ subject choices]. In V. Britschgi, & J. Rautopuro Rantala, J. & Ouakrim-Soivio, N. (2020). Why does changing the orientation of History teachingtake so long? A case study from Finland. In, Berg, C. & Christou, T. (Eds.) The Palgrave handbook of History and Social Studies education. Cham: Palgrave Macmillan, 471–494. Kupiainen, S. & Ouakrim-Soivio, N. (2019). Do centralised upper secondary school exit examinations offer added value? Presentation on NOFA7-konference13.–15.5.2019. Retrieved 15.10.2022 at https://www.diva-portal.org/smash/get/diva2:1347552/FULLTEXT01.pdf Declaration of conflicts of interests: No potential conflict of interest was reported by the authors.